2017
DOI: 10.2141/jpsa.0170028
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the Behavioral Tests for Monitoring Agonistic Behavior of Layer Chicks

Abstract: Chicken agonistic behavior, a type of social behavior related to threatening and fighting, is among the most serious problems in the poultry industry. However, due to luck of effective models for investigating the brain mechanisms of the behavior, no effective measures have been taken. This study, therefore, aimed to select the behavioral tests available for monitoring chicken agonistic behavior. Two behavioral tests, resident-intruder (R-I) test and social interaction (SI) test, were performed for 10 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The R-I test was performed at 29 and 30 days of age and the SI test at 31 and 32 days of age. The TAFs and AER were calculated according to the protocols of Raihan et al (2017) and Yan et al (2019). The TAFs are defined as the sum of the frequencies of pecking, biting, kicking, threatening, and leaping.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The R-I test was performed at 29 and 30 days of age and the SI test at 31 and 32 days of age. The TAFs and AER were calculated according to the protocols of Raihan et al (2017) and Yan et al (2019). The TAFs are defined as the sum of the frequencies of pecking, biting, kicking, threatening, and leaping.…”
Section: Methodsmentioning
confidence: 99%
“…In general, the R-I test is used to monitor territorial aggression induced by invasion of another conspecific to the experimental territory of an animal (Koolhaas et al, 2013), and the SI test is used to study social behavior between two animals, such as sniffing, grooming, and isolation-induced aggressive behavior (Silverman et al, 2010). In our behavioral trials, the resident chicks in the R-I test showed aggressive behavior more frequently than the intruder ones from eight days of age (Raihan et al, 2017). These s results suggest that territorial aggression in chickens is T-independent, because the plasma concentration of T in male chicks is reported to be low until 28 days of age (Tanabe et al, 1979).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The SI test was performed with 32-day-old male layer chicks as described by Raihan et al (2017). After measuring body weight with an electronic scale (HF-2000, A&D Co. Ltd., Tokyo, Japan), a pair of chicks, T-implanted (as an aggressor) and intact (as an opponent), were simultaneously transferred by hand to the diagonal corners of the observation cage (44×30×24 cm, length×width×height), and aggressive behavior of the aggressor and opponent was recorded using a video camera (GZ-R470, JVC KENWOOD Corporation, Kanagawa, Japan).…”
Section: Si Testmentioning
confidence: 99%
“…The R-I test is used to study the territorial aggression induced by intrusion of another conspecific to the experimentally reproduced territory of animals (Koolhaas et al, 2013). To develop effective behavioral models that quantitatively estimate aggressive behavior in chickens, we previously monitored the aggressive behavior of male layer chicks from 8 to 24 days of age using the SI and R-I tests (Raihan et al, 2017). The chicks in the R-I test showed aggressive behavior more frequently than those in the SI test, indicating that the R-I test, rather than the SI test, is more effective in monitoring the aggressive behavior of male layer chicks.…”
Section: Introductionmentioning
confidence: 99%